2015
DOI: 10.1017/etds.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

A good universal weight for nonconventional ergodic averages in norm

Abstract: Abstract. We will show that the sequence appearing in the double recurrence theorem is a good universal weight for the Furstenberg averages.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…where ||| · ||| µ,k is the seminorm on L ∞ (µ) defined in [46] in the ergodic case and in [20] in the general case. 3 We recall the definition and some properties of these seminorms in Appendix A. Note also that if ψ : N d → C is a nilsequence of the form (Φ(T n x)) n∈N d , then ψ admits correlations along every Følner sequence I and…”
Section: Uniformity Seminorms and Decomposition Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ||| · ||| µ,k is the seminorm on L ∞ (µ) defined in [46] in the ergodic case and in [20] in the general case. 3 We recall the definition and some properties of these seminorms in Appendix A. Note also that if ψ : N d → C is a nilsequence of the form (Φ(T n x)) n∈N d , then ψ admits correlations along every Følner sequence I and…”
Section: Uniformity Seminorms and Decomposition Resultsmentioning
confidence: 99%
“…When d = 1, examples of good universal weights for some multiple ergodic averages can be found in [1,2,3,4,19,26,30,32,48,70]. Most of these results deal with the case where ℓ = 1 and are based on the theory of characteristic factors that was pioneered by H. Furstenberg.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the authors showed that the sequence a n = f 1 (T an x) f 2 (T bn x) is a good universal weight for the Furstenberg averages in the L 2 -norm for µ-a.e. x ∈ X [7], which was extended further to the case where we have commuting transformations [8]. The first author extended the double recurrence Wiener-Wintner result to nilsequences [3], and a result similar to this was announced by P. Zorin-Kranich independently [22].…”
Section: Introductionmentioning
confidence: 99%